Effect of music on post-exercise recovery rate in young healthy individuals - Desai, Rajesh Motibhai; Thaker, Ravi B.; Patel, Jitendra R.; Parmar, Jasmin (International Journal of Research in Medical Sciences, 2017)
Background: Music has been used in exercise classes for many decades. The role of music in increasing the exercise performance is well recognized but there is very little information about effect of music on post-exercise recovery time. Methods: The present study was conducted to see the effect of musical sounds on post-exercise recovery time following moderate exercise with Harvard step test in young healthy volunteers. 30 young healthy volunteers (17 males, 13 females) aged between 17 to 20 years were recruited for the study. Pulse rate, systolic BP, diastolic BP were recorded prior to exercise in lying down position. The participants were subjected to moderate exercise by Harvard step test for 3 minutes on 3 consecutive days. They were allowed to rest in silence on 1st day, rest with hearing slow music on 2nd day and rest with hearing fast music on 3rd day. During the post-exercise relaxation time PR, SBP and DBP were measured immediately and after every 1 min. until the parameters returned to resting values. Data was statistically analysed using ANOVA test and 0.05 level of significance was set prior to the study. Results: The result showed that with slow music, recovery time of pulse rate (5.2 ± 2.1), systolic blood pressure (3.9 ± 1.1) and diastolic blood pressure (3.2 ± 1.7) were significantly faster as compared to both no music and fast music. Conclusion: The study concluded that music hastens post-exercise recovery and slow music has greater relaxation effect than fast or no music.